Intra-articular injection of placental mesenchymal stromal cells ameliorates pain and cartilage anabolism/catabolism in knee osteoarthritis - Fan, Mengqiang; Zhang, Jingwen; Zhou, Li; Chen, Zuxiang; Bao, Ronghua; Zheng, Longpo; Tong, Peijian; Ma, Yuhai; Shan, Letian (Frontiers in Pharmacology, 2022)
Background: Knee Osteoarthritis (kOA), the most common joint degenerative disorder, lacks effective therapeutics. Placenta-derived mesenchymal stromal cells (PMSCs) are effective in tissue repairing and generation, which have potential in treating kOA. This study aimed to determine the anti-kOA efficacy of PMSCs and to explore its action mode. Methods: Flow cytometry and three-line differentiation were performed for identification of PMSCs. In vivo, a rat kOA model established by anterior cruciate ligament transection (ACLT) surgery was used to evaluate the efficacy of PMSCs. Histopathological HE and SO staining with Osteoarthritis Research Society International scoring were conducted, and cartilage expressions of MMP13 and Col2 were measured by immunohistochemistry. Pain behavior parameters by mechanical withdrawal threshold (MWT) and thermal withdrawal latency (TWL), were measured. In vitro, wound healing and cell immunofluorescence assays were conducted to detect the proliferation and migration ability of chondrocytes treated with PMSCs conditioned medium (PMSCs-CM). Quantitative real-time PCR (qRT-PCR) and Western blot (WB) assays were applied to explore the molecular action of PMSCs on chondrocytes. Results: The results of flow cytometry indicated that the surface markers of PMSCs (CD73 > 95%, CD90 > 95%, and CD34 < 2%) were consistent with the typical mesenchymal stromal cells. The in vivo data showed that PMSCs significantly reversed the kOA progression by protection of cartilage, regulation of anabolic (Col2) and catabolic (MMP13) expressions, and relief of pain symptoms. The in vitro data showed that PMSCs promoted chondrocyte proliferation and migration and significantly restored the IL-1β-induced abnormal gene expressions of Col2, Mmp13, Adamts4, Adamts5 and Sox9 and also restored the abnormal protein expressions of Col2, Mmp13 and Sox9 of chondrocytes. The molecular actions of PMSCs on chondrocytes in nested co-culture way or in conditioned medium way were similar, confirming a paracrine-based mode of action. Conclusion: This study demonstrated PMSCs’ anti-kOA efficacy and its paracrine-based action mode, providing novel knowledge of PMSCs and suggesting it as a promising cell therapy for treatment of kOA.